Changing world, changing teacher education: a tribute to Geoff Whitty (1946-2018). Issue 1 (1st January 2020) - Menter, Ian
ABSTRACT: This paper is based on a keynote address given at the ATEE Annual Conference 2019, held at Bath Spa University, remembering Geoff Whitty (1946–2018). It seeks to make sense of the current teacher education scene, both within the United Kingdom and across Europe and beyond. Reference will be made to Whitty's enormous contribution to our understanding of policy processes in teacher education as well as to the author's own work, much of it inspired by Whitty. The paper concludes with suggestions for a focused international research agenda for teacher education, that is viable in a Europe where the UK may have left the Union and in a wider world where global politics are unpredictable and where the meaning of 'truth' is frequently called into question.